PENENTUAN KOMPOSISI ATMOSFIR UNTUK PENYIMPANAN BAWANG DAUN RAJANGAN - Sugiarto, Hadikaria Purwadaria dan Illah Sailah (Department of Agroindustrial Technology, Bogor Agricultural University, 2005)
ABSTRACTShredded leek is highly perishable and needs appropriate storage condition for longer shelflife. One of the storage techniques is modified atmosphere combined with cold storage. At ambient temperature storage, shredded leek has only a 3 day shelflife. The research results indicated that storing shredded leek at lower temperature provided a longer shelflife : 10 days at 10 oC and 20 days at 5 oC. The respiration rate at early storage period is 197 ml O2/kg.hr and 197 ml CO2/kg.hr. The atmospheric composition 3-5% oxygen and 3-5% carbondioxide provided the best result of 14 days for the shelflife of shredded leek. During the modified atmosphere storage the shredded leek experienced 8% total weight loss, increasing their lightness from 33 to 33,5, increasing their a value (red-green color) from (-)9,84 to (-4), but did not show significant sensory value changes.Key words : penyimpanan atmosfir termodifikasi, laju respirasi, terolah minimal